2021
DOI: 10.1093/texcom/tgab003
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation during Thoughts of One’s Own Death and Its Linear and Curvilinear Correlations with Fear of Death in Elderly Individuals: An fMRI Study

Abstract: Facing one’s own death and managing the fear of death are important existential issues, particularly in older populations. Although recent functional magnetic resonance imaging (fMRI) studies have investigated brain responses to death-related stimuli, none has examined whether this brain activation was specific to one’s own death or how it was related to dispositional fear of death. In this study, during fMRI, 34 elderly participants (aged, 60–72 years) were presented with either death-related or death-unrelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Trait mindfulness was correlated with prosocial behavior ( Donald et al, 2019 ) and reduced PCC activation was observed during mindful acceptance of emotions ( Messina et al, 2021 ). However, the relationship between PCC activation and adaptability may be nonlinear; fear of death and PCC activation exhibited a quadratic relationship during the contemplation of one’s own death ( Hirano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trait mindfulness was correlated with prosocial behavior ( Donald et al, 2019 ) and reduced PCC activation was observed during mindful acceptance of emotions ( Messina et al, 2021 ). However, the relationship between PCC activation and adaptability may be nonlinear; fear of death and PCC activation exhibited a quadratic relationship during the contemplation of one’s own death ( Hirano et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trait mindfulness has been shown to be correlated with prosocial behavior (Donald et al, 2019) and reduced PCC activation was observed during mindful acceptance of emotion (Messina et al, 2021). However, the relationship between PCC activation and adaptability may be nonlinear; fear of death and PCC activation were shown to have a quadratic relationship during the contemplation of one's own death (Hirano et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This study analyzed a dataset that had originally been obtained for different research purposes ( Hirano et al, 2021 ). In the original experiment, participants were asked to judge the relevance of the presented word to themselves or other individuals.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have examined the neural response to mortality threat, typically contrasting it with negative emotional conditions (e.g., dental pain). They demonstrated increased activity in the amygdala ( Quirin et al, 2012 ) and various frontoparietal regions ( Yanagisawa et al, 2016 ; Klackl et al, 2018 ; Qin et al, 2018 ; Hirano et al, 2021 ), decreased activity in the insular cortex ( Han et al, 2010 ; Shi and Han, 2013 ; Klackl et al, 2014 ; Qin et al, 2018 ), and increase ( Quirin et al, 2012 ) and decrease ( Qin et al, 2018 ) in the activity in the anterior cingulate cortex. However, few studies have investigated individual differences in neural activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation